Quantitative Examination of Gastropod and Soil Relationships in an Oak-Hickory Forest in the Lower Illinois Valley Region - Roy Stanley Riggle (Hello World!, 1976)
Malacology can contribute significantly to the reconstruction of the local ecology at archaeological sites. Detailed reconstructions, however, are hampered by the paucity of molluscan ecological information, particularly at the local level. Seven soil variables and their effects on the distribution of thirteen snail species were examined for part of a mesic oak-hickory stand in the lower Illinois Valley region. Generalized relationships between soil variables and snails were apparent. The number of species, and less so the number of specimens, tends to increase as the sample area increases. Traditional methods of graphic analysis and bivariate statistics did not provide optimal information on underlying relationships between the data sets. Few significant bivariate correlations were obtained between snail species and soil variables.